2022
DOI: 10.48550/arxiv.2204.07288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the Efficiency vs. Accuracy Trade-off for Long-Context NLP Models

Abstract: With many real-world applications of Natural Language Processing (NLP) comprising of long texts, there has been a rise in NLP benchmarks that measure the accuracy of models that can handle longer input sequences. However, these benchmarks do not consider the trade-offs between accuracy, speed, and power consumption as input sizes or model sizes are varied. In this work, we perform a systematic study of this accuracy vs. efficiency trade-off on two widely used long-sequence models -Longformer-Encoder-Decoder (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…This is due to the need for extensive cloud computing resources and prolonged training times. Additionally, it has been observed that improving the accuracy of an AI model beyond a specific threshold tends to require exponentially more computational resources, which in turn can lead to increased environmental and economic costs [61,75,156,169,171,172]. In addition, choosing cloud instances by region and operation time can notably lower carbon emissions [50,59,72].…”
Section: Data Managementmentioning
confidence: 99%
“…This is due to the need for extensive cloud computing resources and prolonged training times. Additionally, it has been observed that improving the accuracy of an AI model beyond a specific threshold tends to require exponentially more computational resources, which in turn can lead to increased environmental and economic costs [61,75,156,169,171,172]. In addition, choosing cloud instances by region and operation time can notably lower carbon emissions [50,59,72].…”
Section: Data Managementmentioning
confidence: 99%